miR-22-3p/PGC1β Suppresses Breast Cancer Cell Tumorigenesis via PPARγ - Xuehui Wang; Zhilu Yao; Lin Fang (PPAR Research)
In this study, we found that miR-22-3p expression was decreased in breast cancer (BC) cell lines and tissues. Overexpression of miR-22-3p inhibited the proliferation and migration of BC cells in vitro and in vivo, while depletion of miR-22-3p exhibited the opposite effect. Importantly, miR-22-3p could directly target PGC1β and finally regulate the PPARγ pathway in BC. In conclusion, miR-22-3p/PGC1β suppresses BC cell tumorigenesis via PPARγ, which may become a potential biomarker and therapeutic target.